2013
DOI: 10.1016/j.jmoldx.2013.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Detection of BRAF V600 Mutations in Metastatic Melanoma

Abstract: Detection of the BRAF V600E mutation is required for use of the BRAF inhibitor, vemurafenib, in patients with metastatic melanoma. Although the Roche Cobas 4800 BRAF V600 Mutation Test is approved, it detects primarily the single-nucleotide V600E mutation and could miss other potentially relevant V600 mutations. To assess the detection rate of the cobas assay for V600 mutations in clinical specimens, we compared the results of this assay with Sanger sequencing in 295 melanoma FFPE samples. Twenty samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 21 publications
0
16
0
1
Order By: Relevance
“…Details about testing protocols are described elsewhere. [1315] In selected cases mutational status was analyzed using a standardized real-time PCR (COBAS ® 4800) system provided by Roche. [15] The BRAF mutation was determined on the most recent available tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…Details about testing protocols are described elsewhere. [1315] In selected cases mutational status was analyzed using a standardized real-time PCR (COBAS ® 4800) system provided by Roche. [15] The BRAF mutation was determined on the most recent available tumor tissue.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, pathologist-generated estimates of tumor cellularity served as a QA measure for a clinical BRAF pyrosequencing assay. Detection of a lower-than-expected p.V600E signal in specimens with a high tumor cellularity prompted an investigation, which revealed that our original pyrosequencing assay, similar to the Cobas 4800 BRAF V600 mutation test [2224, 35, 36], may show a weak p.V600E signal in p.V600K positive specimens. Our revised pyrosequencing assay could distinguish p.V600E mutation from other non-p.V600E mutations and confirmed a higher incidence of p.V600K mutation than previously reported in melanomas [4, 6, 911].…”
Section: Discussionmentioning
confidence: 99%
“…However, the probes have been shown to also cross-hybridize with the p.V600K allele and other non-p.V600E mutant alleles such as p.V600D [2224, 35, 36]. In addition, Cobas 4800 and other PCR-based assays detect non-p.V600E mutations with a lower analytic sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations